2009
DOI: 10.1002/jcb.22462
|View full text |Cite
|
Sign up to set email alerts
|

Bone morphogenic protein 2 directly enhances differentiation of murine osteoclast precursors

Abstract: Previous studies found that BMPs support osteoclast formation, but it is not clear whether this is a direct effect on osteoclasts or mediated indirectly through osteoblasts. We have shown that a mouse deficient for the BMP antagonist Twisted gastrulation suggested a direct positive role for BMPs on osteoclastogenesis. In this report, we further determine the significance of BMP signaling on osteoclast formation in vitro. We find that BMP2 synergizes with suboptimal levels of RANKL to enhance in vitro different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
128
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(149 citation statements)
references
References 42 publications
21
128
0
Order By: Relevance
“…The high-bone-mass phenotype in mice with osteoblast-specific Bmpr1a silencing was found to be triggered by impaired expression of sclerostin (SOST) (Kamiya et al 2008), an antagonist of Wnt signaling that acts by sequestering the co-receptor low-density lipoprotein receptor-related protein 5 (LRP5) into inactive complexes (van Bezooijen et al 2007;Kamiya et al 2010;Krause et al 2010), as also discussed below in the context of sclerosteosis and Van Buchem disease. In addition, treatment of osteoclastic precursors with BMP induces differentiation along the osteoclast cell lineage, and further stimulates expression of key enzymes for bone degradation (Kaneko et al 2000;Jensen et al 2010). The observation that BMP can regulate both bone formation and bone resorption is consistent with the notion that, with the exception of fibrodysplasia ossificans progressiva (FOP), mutations in BMP signaling components do not generally cause anabolic bone diseases.…”
Section: Tgf-b Family Signaling In Connective Tissuesmentioning
confidence: 85%
See 1 more Smart Citation
“…The high-bone-mass phenotype in mice with osteoblast-specific Bmpr1a silencing was found to be triggered by impaired expression of sclerostin (SOST) (Kamiya et al 2008), an antagonist of Wnt signaling that acts by sequestering the co-receptor low-density lipoprotein receptor-related protein 5 (LRP5) into inactive complexes (van Bezooijen et al 2007;Kamiya et al 2010;Krause et al 2010), as also discussed below in the context of sclerosteosis and Van Buchem disease. In addition, treatment of osteoclastic precursors with BMP induces differentiation along the osteoclast cell lineage, and further stimulates expression of key enzymes for bone degradation (Kaneko et al 2000;Jensen et al 2010). The observation that BMP can regulate both bone formation and bone resorption is consistent with the notion that, with the exception of fibrodysplasia ossificans progressiva (FOP), mutations in BMP signaling components do not generally cause anabolic bone diseases.…”
Section: Tgf-b Family Signaling In Connective Tissuesmentioning
confidence: 85%
“…This effect is in part mediated by the BMP-dependent increase of OPG expression in osteoblasts, and consequent suppression of osteoclast differentiation (Kaneko et al 2000;Wan et al 2001;Jensen et al 2010;Kamiya and Mishina 2011). However, BMP signaling also regulates bone resorption, as is apparent by the high bone mass phenotype when Bmpr1a expression is specifically inactivated in osteoblasts, which results in failed osteoclastogenesis (Kamiya et al 2008).…”
Section: Tgf-b Family Signaling In Connective Tissuesmentioning
confidence: 99%
“…45 Osteoclastogenesis could then be occurring in the ectopically implanted ACS site due to differentiation of HPCs (monocyte-macrophage lineage) to osteoclasts, particularly in the presence of rhBMP-2 and rhBMP-2 induced osteoblastic differentiation of recruited MSCs. 55 Reports by other groups have previously shown evidence that SDF-1 plays a crucial regulatory role in BMP-2 induced osteogenic differentiation of MSCs. Hosogane et al showed that BMP-2-induced alkaline phosphatase (ALP) activity, osteocalcin (OC) synthesis, and calcium deposition was significantly decreased by blocking the SDF-1/CXCR4 signal axis with AMD3100.…”
Section: Sdf-1/cxcr4 Axis and Bone Formationmentioning
confidence: 97%
“…We found the opposite in this study, which suggests that BMP2 may also be involved in regulating periosteal bone resorption. In recent years, studies have in fact found that BMP2 can enhance osteoclastogenesis indirectly by stimulating osteoblasts or stromal cells to produce osteoclast-promoting factors, such as RANKL (Abe et al, 2000;Otsuka et al, 2003), or directly by activating osteoclast differentiation in the presence of RANKL (Jensen et al, 2009). It is hence likely that stronger expression of BMP2 at the anterior periosteal region plays an assisting role in promoting osteoclastogenesis by synergizing with RANKL.…”
Section: Discussionmentioning
confidence: 99%